Typology Of Muslim Family Welfare In Pontianak City Utilizing The Cibest Approach - Arminingsih, Diah; Taufik, Iman; Mubaraq, Abd (ITB AAS INDONESIA Surakarta, 2024)
The aim of this research is to present an Islamic perspective overview of the typology of muslim family welfare in Pontianak City, focusing on the fulfillment of both material and spiritual welfare indicators. The research employs a quantitative approach with a descriptive methodology, utilizing primary data sources complemented by secondary data. The population source comprises all muslim families in Pontianak City, spanning six sub-districts: South Pontianak, Southeast Pontianak, East Pontianak, West Pontianak, Pontianak Kota, and North Pontianak. Accidental sampling is employed as the sampling technique, resulting in a total sample size of 90 respondents. The analysis tool employed is the CIBEST measuring instrument, categorizing the CIBEST Quadrant into four areas: welfare, spiritual poverty, material poverty, and absolute poverty. The findings reveal a typology of muslim family welfare in Pontianak City, divided into two quadrants: 1) Quadrant I (Material and spiritual welfare) with the highest percentage among other quadrants, and 2) Quadrant II (Material poverty) with a percentage of less than 5 families.